The chiisanoside derivatives present in the leaves of Acanthopanax sessiliflorus activate autophagy through the LRP6/GSK3β axis and thereafter inhibit oxidative stress, thereby counteracting cisplatin-induced ototoxicity - Wenxin Zhang; Wenxin Zhang; Hongbo Teng; Hongbo Teng; Tianyi Zhao; Tianyi Zhao; Roberts I. Eglitis; Xv Wang; Xv Wang; Zhengxuan Yu; Shurong Qu; Shurong Qu; et al. (Frontiers in Pharmacology)
IntroductionCisplatin is extensively employed in the treatment of multiple solid malignant tumors. Nevertheless, side effects such as cisplatin-induced ototoxicity (CIO) pose obstacles to tumor therapy.The important natural product chiisanoside from Acanthopanax sessiliflorus has abundant activity against CIO.MethodsIn this study, 26 chiisanoside derivatives were screened, and compound 19 demonstrated significant protective activity against CIO damage. A cisplatin—induced HEI—OC1 cell injury model and a mouse ototoxicity model were established. The regulatory effects were revealed through transcriptome sequencing, and the protein expression levels were analyzed by molecular docking, ELISA, Western blotting, and immunofluorescence.ResultsIt was found that compound 19 inhibited cell apoptosis, alleviated abnormal hearing and spiral ganglion damage. Transcriptome sequencing revealed its regulatory effects. Compound 19 treatment increased autophagy levels, thereby alleviating mitochondrial dysfunction and reducing the accumulation of reactive oxygen species (ROS).In-depth studies have found that the autophagy inhibitor 3-methyladenine (3-MA) weakens the regulatory effect of compound 19 on autophagy and inhibits the clearance of damaged cells, resulting in oxidative stress damage, apoptosis and necrosis. By knocking down LRP6, it was found that the protective effect of compound 19 was eliminated, the autophagy level was significantly reduced, oxidative stress and ROS production were induced, and apoptosis after cisplatin exposure was promoted. Finally, the inhibitor LiCl was used to suppress the expression of GSK3β. It was found that inhibiting GSK3β could protect cells from cisplatin-induced damage by activating autophagy.DiscussionThese findings suggest that compound 19 is capable of preventing ototoxicity by activating autophagy via the LRP6/GSK3β axis and consequently inhibiting oxidative stress, offering a new approach for treating CIO and sensorineural hearing loss.